Historicizing the Apostolic Faith Mission in the United Kingdom - Sande, Nomatter (Journal of pentecostal theology, 2019)
This article presents a history of the Apostolic Faith Mission in the United Kingdom from an academic perspective. More specifically, the article discusses the emergence of the Apostolic Faith International Ministries UK (afmimuk). Arguably, the afmimuk is regarded as a missionary field of the Apostolic Faith Mission of Zimbabwe. So, the article discusses the early 20 years of the Apostolic Faith Mission in the United Kingdom. The lack of previous documentation presents a challenge to the writing of the denomination's history. The article uses historiography by objective (hbo) as a theoretical framework and concludes that the afmimuk is an example of the spread of Pentecostal Christianity in Europe.